2021
DOI: 10.3390/app11073135
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Analysis in Applications of Active Mono-Slip and Continuum Dislocations in the MDCM

Abstract: The key purpose of this paper is to propose a mono-slip-dependent continuum dislocation method for matrix-dominated composite structure (MDCS) analysis. The methodology focuses on dissipation energy theories utilizing a continuum dislocation method (CDM) integrated with small-strain kinematics. The mathematical modeling of the CDM comprises active mono-slip system formulations, thermodynamic dislocation analysis (TDA), free energy dissipation analysis, and the progression of dislocations. Furthermore, zero and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…3,4 Kasa presented an improved higher order layer-wise theory for the investigation of flawlessly wedged sandwich-composite beams with general laminate configurations and proposed a simple approach based on continuum dislocation theory to analyze the plastic phenomenon of matrix-dominated composite exposed to shear. 5,6 Li et al 7 and Omachi et al 8 showed failure mechanisms of sandwich lattice constructions. Simsek et al used finite-element (FE) modeling and modal testing to investigate the dynamic performances of gyroid structures made of HS188 and manufactured with direct metal laser melting.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Kasa presented an improved higher order layer-wise theory for the investigation of flawlessly wedged sandwich-composite beams with general laminate configurations and proposed a simple approach based on continuum dislocation theory to analyze the plastic phenomenon of matrix-dominated composite exposed to shear. 5,6 Li et al 7 and Omachi et al 8 showed failure mechanisms of sandwich lattice constructions. Simsek et al used finite-element (FE) modeling and modal testing to investigate the dynamic performances of gyroid structures made of HS188 and manufactured with direct metal laser melting.…”
Section: Introductionmentioning
confidence: 99%